"Vivant de dignité de douleurs et d'alarmes": Personalism in André Ulmann's Poèmes du camp. Issue 3 (December 2018) - Joseph, Belle
Abstract : Although Holocaust literature is an active and ever-growing field of research, little attention has been paid to the large corpus of French poetry written in the concentration camps by Jews and Resistants. In this article, I investigate the poetry that French journalist and political activist André Ulmann wrote during his imprisonment in Mauthausen, published in 1969 as Poèmes du camp, reading these texts in the light of the author's involvement in the early personalist movement. I explore how these poems, which describe the author's efforts to practise unflinching awareness of himself and his circumstances, and to retain personal freedom despite his captivity, are deeply informed by personalist doctrine on the inalienable freedom and self-determination proper to each individual. The continuity of Ulmann's beliefs during his captivity calls into question existing scholarship on the Nazi concentration camps, which casts this historical phenomenon as a devastating rupture with preceding intellectual and spiritual frameworks.